2020
DOI: 10.1186/s13014-020-01572-w
|View full text |Cite
|
Sign up to set email alerts
|

Stability and reproducibility of 6013 deep inspiration breath-holds in left-sided breast cancer

Abstract: Purpose: Patients with left-sided breast cancer frequently receive deep inspiration breath-hold (DIBH) radiotherapy to reduce the risk of cardiac side effects. The aim of the present study was to analyze intra-breath-hold stability and inter-fraction breath-hold reproducibility in clinical practice. Material and methods: Overall, we analyzed 103 patients receiving left-sided breast cancer radiotherapy using a surface-guided DIBH technique. During each treatment session the vertical motion of the patient was co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
36
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(43 citation statements)
references
References 29 publications
5
36
2
Order By: Relevance
“…Similar deviations are observed; between 1 and 2 mm of median intra-breath hold deviation. Surface scanning based gating shows better intra breath-hold stability, as was measured by Reitz et al [23] using a linear fit, similar to our approach. They detect median drift of only 0.4 mm within the gating window.…”
Section: Discussionsupporting
confidence: 83%
“…Similar deviations are observed; between 1 and 2 mm of median intra-breath hold deviation. Surface scanning based gating shows better intra breath-hold stability, as was measured by Reitz et al [23] using a linear fit, similar to our approach. They detect median drift of only 0.4 mm within the gating window.…”
Section: Discussionsupporting
confidence: 83%
“…SGRT systems offer the possibility of evaluating intra-DIBH stability, which has been reported with ≤0.7 mm, together with an intra-fractional reproducibility of ≤2.2 mm [68] and with 0.3 mm as the median standard deviation of the BH level during DIBH [69]. Kügele et al reported that the intrafractional reproducibility for tangential and locoregional treatment was as low as 1 mm (median over 40 patients) in all three translational directions, but during a single treatment session the maximum deviation was up to 5 mm, which resulted in large effects on the target coverage and OAR doses [70].…”
Section: Breath-holdmentioning
confidence: 99%
“…These setup margins were large, and so the errors would be overestimated. Recent reports evaluated intra- and inter-fractional chest wall motion during DIBH [ 19 , 21 ]. However, there are no reports that effectively provide appropriate PTV margins without overestimation of systematic errors.…”
Section: Introductionmentioning
confidence: 99%